Assessing Impression Management in South African District Municipalities’ Annual Reports: A Textual Characteristics Analysis of Mayor’s Foreword - Phesa, Masibulele; Mgoyana, Sithandiwe (Yayasan Ilomata, 2024)
The study delves into the strategic use of impression management within South African district municipalities, examining how this phenomenon manifests in their annual reports, particularly in the mayor’s foreword. These forewords, being the first statement in the annual report, often employ opportunistic and overly optimistic language that can obscure the true state of municipal performance, creating ambiguity for the public. Using quantitative content analysis, the research scrutinized annual reports from a sample of 34 district municipalities. The findings revealed significant evidence of impression management tactics. Notably, non-performing municipalities tended to produce lengthier mayor’s forewords compared to their performing counterparts. Both categories frequently employed passive constructions and personalized references, aiming to shape perceptions and claim credit selectively. By shedding light on these practices, the study adds to the growing discourse on transparency in local governance. It underscores the need for vigilance, warning the public about how such rhetorical strategies can conceal service delivery shortcomings. This research also contributes valuable insights into the mechanisms of self-attribution in government communications, urging citizens to critically evaluate municipal reports.